Tourism Marketing Communication: A Case Study at The Tourism Office of Pasuruan Regency - Faqeh, Muhammad Syaifulloh; Rakhmawati, Antin (Manunggal Halim Jaya, 2025)
This research examines the tourism marketing communication strategies implemented by the Pasuruan Regency Tourism Office, considering the region's significant potential yet facing challenges in the digital era. Aiming to identify existing strategies and formulate effective innovations, this study employs a descriptive qualitative method. Data collection involved observation, interviews, and documentation, analyzed through data reduction, display, and conclusion drawing. Findings reveal the office has implemented comprehensive and integrated strategies through meticulous market segmentation, targeting, and positioning. Integrated Marketing Communication, predominantly utilizing digital media and influencer collaborations, complemented by offline promotions, serves as a core pillar. This holistic approach proves effective in informing, persuading, and building tourist loyalty, contributing to the sustainable development of the tourism sector and local economy.